2015
DOI: 10.1002/2014wr016653
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing water resources management in large river basins with integrated surface water‐groundwater modeling: A surrogate‐based approach

Abstract: Integrated surface water-groundwater modeling can provide a comprehensive and coherent understanding on basin-scale water cycle, but its high computational cost has impeded its application in real-world management. This study developed a new surrogate-based approach, SOIM (Surrogate-based Optimization for Integrated surface water-groundwater Modeling), to incorporate the integrated modeling into water management optimization. Its applicability and advantages were evaluated and validated through an optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 62 publications
0
39
0
1
Order By: Relevance
“…Since groundwater recharge plays a critical role in sustaining a healthy ecosystem in the lower stream, it is important to consider the impact of groundwater abstraction together with the reservoir operational strategies. As our previous study [28] revealed, for the Middle HRB, if more groundwater is used in the irrigation districts that are closer to the river and more river water is diverted to the districts that are further away from the river, the water use efficiency for irrigation may be increased. Experiment B is designed to represent this spatial operation of the groundwater reservoir, in which the changes in pumping ratio at different irrigation districts follow the suggestion by Wu et al [28].…”
Section: Numerical Modeling Experimentsmentioning
confidence: 89%
See 1 more Smart Citation
“…Since groundwater recharge plays a critical role in sustaining a healthy ecosystem in the lower stream, it is important to consider the impact of groundwater abstraction together with the reservoir operational strategies. As our previous study [28] revealed, for the Middle HRB, if more groundwater is used in the irrigation districts that are closer to the river and more river water is diverted to the districts that are further away from the river, the water use efficiency for irrigation may be increased. Experiment B is designed to represent this spatial operation of the groundwater reservoir, in which the changes in pumping ratio at different irrigation districts follow the suggestion by Wu et al [28].…”
Section: Numerical Modeling Experimentsmentioning
confidence: 89%
“…As our previous study [28] revealed, for the Middle HRB, if more groundwater is used in the irrigation districts that are closer to the river and more river water is diverted to the districts that are further away from the river, the water use efficiency for irrigation may be increased. Experiment B is designed to represent this spatial operation of the groundwater reservoir, in which the changes in pumping ratio at different irrigation districts follow the suggestion by Wu et al [28]. The pumping ratio is defined as the percentage of groundwater in the total irrigation water supply.…”
Section: Numerical Modeling Experimentsmentioning
confidence: 89%
“…The interactions between surface water and groundwater are substantial and complex in the HRB [28]. The HRB has been affected by significant human-nature water conflicts (i.e., midstream vs. downstream, and agriculture vs. ecological services), as discussed in previous studies [28][29][30].…”
Section: Study Areamentioning
confidence: 92%
“…Groundwater discharges to river or as springs at the middle part of the study area. In our previous study, we performed integrated surface water-groundwater modeling using GSFLOW [34] to study the complex water cycle of the HRB and its response to human activities [29,31,35]. It has been found that this area has significant surface water-groundwater interaction, and the interaction is complicated by intensive pumping and irrigation [30,31,35].…”
Section: Study Areamentioning
confidence: 99%
“…Sadeghi-Tabas et al proposed an attempt to link MODFLOW to a multi-algorithm genetically adaptive search method (AMALGAM) to optimize pumping rates of a groundwater system in Iran [17]. A surrogate-based approach was developed based on integrated surface water-groundwater modeling to optimize the percentages of surface water and groundwater in irrigation water in order to obtain a better balance between groundwater storage in the middle reaches of HRB and the environmental flow in the lower reaches [18]. Hamid R. Safavi and Mehrdad Falsafioun combined a genetic algorithm optimization model with scenario analysis to develop an optimal plan for the conjunctive use of surface water and groundwater resources in Zayandehrud Basin, Iran [19].…”
Section: Related Workmentioning
confidence: 99%